PENGEMBANGAN MODUL FISIKA PADA MATERI FLUIDA MATA KULIAH FISIKA DASAR I UNIVERSITAS JAMBI - Melinda; Hendri, Menza; Dani, Rahma (EduFisika: Jurnal Pendidikan Fisika, 2019)
The purpose of this research is to produce a physics learning module on fluid material and to know the student's perception of the module. This research includes research and development. The development Model used is ADDIE (Analyze, Design, Development, Implementation, and Evaluation). The Physics learning module on the fluid material of basic Physics 1 courses has been declared worthy by the validator. Test Result module obtained 85 (very good) for the design aspects of learning, the material aspect is 85.07 (very good), the aspect of readability module is 85.22 (very good), the visualization aspect of the module is 84.11 (very good). The basic Physics Module 1 development fluid material is worth using as one of the learning teaching materials in the classroom.